2017
DOI: 10.1002/ccd.27246
|View full text |Cite
|
Sign up to set email alerts
|

Single trans‐septal access technique for left atrial intracardiac echocardiography to guide left atrial appendage closure

Abstract: This initial experience suggests that LAA occlusion with the Amplatzer Amulet device using ICE guidance from the left atrium via a single trans-septal technique is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Transoesophageal echocardiography (TOE) is currently the gold standard imaging modality for the guidance of LAAO . However, intracardiac echocardiography (ICE) is now being used to guide a multitude of percutaneous interventions for structural heart disease and its utility in guiding percutaneous LAAO has been suggested by several studies …”
Section: Introductionmentioning
confidence: 99%
“…Transoesophageal echocardiography (TOE) is currently the gold standard imaging modality for the guidance of LAAO . However, intracardiac echocardiography (ICE) is now being used to guide a multitude of percutaneous interventions for structural heart disease and its utility in guiding percutaneous LAAO has been suggested by several studies …”
Section: Introductionmentioning
confidence: 99%
“…No heterogeneity or publication bias was found. In the 15 eligible studies, the technical success rates, which were not estimated, between the ICE and TEE groups were equal to 100% in 7 studies (Aguirre et al, 2018;Berti et al, 2018;Clemente et al, 2015;Frangieh et al, 2017;Hemam et al, 2019;Ho et al, 2007;Matsuo et al, 2016). The pooled effects were driven by the remaining 8 studies (Berti et al, 2014;Frikha et al, 2016;Iwasawa et al, 2016;Kim et al, 2018;Korsholm et al, 2017;Masson et al, 2015;Naim et al, 2015;Reis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The baseline information of the included studies is reported in Table 1. Patients were mainly from Europe (7 studies) (Berti et al, 2014(Berti et al, , 2018Clemente et al, 2015;Frangieh et al, 2017;Korsholm et al, 2017;Matsuo et al, 2016;Reis et al, 2018), the Asia-Pacific region and the US (8 studies) (Aguirre et al, 2018;Frikha et al, 2016;Hemam et al, 2019;Ho et al, 2007;Iwasawa et al, 2016;Kim et al, 2018;Masson et al, 2015;Naim et al, 2015). There were 827 patients in the ICE group and 1236 patients in the TEE group.…”
Section: Study and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aguirre et al describe left atrial appendage occlusion (LAAO) using the Amulet device with fluoroscopic and intra‐cardiac echo (ICE) imaging for guidance . They add the novel technical simplification of utilizing a single transseptal puncture to introduce both the ICE catheter along with the LAAO delivery catheter directly into the LA, rather than using two separate transseptal punctures.…”
mentioning
confidence: 99%